KINERJA SHARIAH BUILDING CONSTRUCTION COMPANY ANTARA SEBELUM DAN SESUDAH PELAKSANAAN PEMBANGUNAN INFRASTRUKTUR NASIONAL - Ari Kristin Prasetyoningrum; Puji Slamet Mulyadi (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2019)
Building construction industry is considered to have a strategic role in national infrastructure development. Through the 2015-2019 National Medium Term Development Plan (RPJMN), national development is gradually being realized by the government to achieve community prosperity. It is indicated that the implementation of infrastructure development affects the net income of related companies, both nominal and percentage (net profit margin). This study is intended to determine the difference in net income of building construction companies before and after the implementation of the 2015-2019 RPJMN 2015-2017 period.This study was tested using paired samples t-test to examine differences in net income of the companies sampled before and after the implementation of the 2015-2019 RPJMN. The sampling method was purposive sampling, so that four issuers were sampled, namely WIKA, ADHI, WSKT, and PTPP.The results showed that the sample data were normally distributed. The first hypothesis was rejected because the results of paired samples t-test showed the value of Sig. (0.003) <α (0.05). Similar rejection occurs in the second hypothesis indicated by the value of Sig. (0.009) <α (0.05). With these results, it can be concluded that there is a difference between net income and net profit margins in building construction companies listed in the JII 2011-2017 period before and after the implementation of national infrastructure development.